Gendering the Mixed Economies of Welfare: Ruptures and Trajectories in Postwar Europe. Introduction - Avdela, Efi; Earner-Byrne, Lindsey; Lampropoulou, Dimitra (Historein, 2024)
The Introduction explains the usefulness of the term “mixed economy of welfare”, the crucial role of gender in its formation and the different meanings of “postwar” in the national case studies included in the special issue. It also previews the six articles of the issue and highlights the often unexpected similarities between them.